4(3x+5)-2(4x-3)=

Simple and best practice solution for 4(3x+5)-2(4x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+5)-2(4x-3)= equation:


Simplifying
4(3x + 5) + -2(4x + -3) = 0

Reorder the terms:
4(5 + 3x) + -2(4x + -3) = 0
(5 * 4 + 3x * 4) + -2(4x + -3) = 0
(20 + 12x) + -2(4x + -3) = 0

Reorder the terms:
20 + 12x + -2(-3 + 4x) = 0
20 + 12x + (-3 * -2 + 4x * -2) = 0
20 + 12x + (6 + -8x) = 0

Reorder the terms:
20 + 6 + 12x + -8x = 0

Combine like terms: 20 + 6 = 26
26 + 12x + -8x = 0

Combine like terms: 12x + -8x = 4x
26 + 4x = 0

Solving
26 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 4x = 0 + -26

Combine like terms: 26 + -26 = 0
0 + 4x = 0 + -26
4x = 0 + -26

Combine like terms: 0 + -26 = -26
4x = -26

Divide each side by '4'.
x = -6.5

Simplifying
x = -6.5

See similar equations:

| x^4-8x^3+15x^2+4x-20=0 | | 4.2=c/0.7 | | c-10=-22 | | 4a-16=a-5 | | 16-n/8=-6 | | -2x-9=11+3x | | 21x^2-18x-5=0 | | 7x+3=24+4x | | 8x^3+x^2-55x+42=0 | | x^5-3x^4+10=0 | | 2x^3-6x+3=0 | | -32-3x=5x-37 | | 2=x^2-8+5 | | 1+2x^2-x^4=0 | | 3x(x-5)=4x | | 3(a+2)=-5-2(a-3) | | w/7+9=-3 | | -3(3d-2)=4-d | | 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t |

Equations solver categories